The Role of Commonality between CEO and Divisional Managers in Internal Capital Markets - Gaspar, José-Miguel; Massa, Massimo (Journal of Financial and Quantitative Analysis, 2011)
Abstract We study the role played by the informal links, or “connections,” between the chief executive officer (CEO) and the divisional managers of conglomerate organizations. Using data on a large sample of multisegment U.S. corporations from 1996 to 2004, we show that segments run by connected managers receive more investment and exhibit lower sensitivity to cash flow shortfalls (and exhibit higher sensitivity to other segments’ cash flow). At the firm level, having more connected managers presiding over segments with high Tobin’s Q improves resource allocation and increases firm value. These findings are consistent with the hypothesis that the mutual trust associated with connections reduces the need for wasteful reallocation of resources across divisions of conglomerate firms.